Strategi Politis untuk Bertahan: Studi Kasus Komunitas Samin di Kudus - Moh - Rosyid (Politea : Jurnal Politik Islam, 2020)
The purpose of this article is describing the ways of Samin people in Kudus, Central Java endeavor of maintain social life. The data by means of interviews, observation, and documentation by descriptif qualitatif. Samin community face problems are carried away by lifestyle the impact of information technology utilization, the religion Adam his believes religion not recognized by the state, lack of similiarity in to interpret religious teachings Ki Samin the source of the speech teachings. The effect, Samin teachings there is something contradictory to law. Estrangement occurs social interaction. The impact, voicing aspirations the authorities did not respond. Efforts made Samin community (1) voicing his aspirations to local figures so that their basic rights are recognized government as religious and married state recognized, (2) networking by nation government organization, jurnalis, lecture, and Samin figure in another district. The results of his efforts, very much determined by seriousness and consistence Samin community in optimizing efforts to the government.